Artistic Practice: notes from the inside – One for One – Ruminative Walks by Vera Mantero & guests - Santos, Maíra (Revista Brasileira de Estudos da Presença, 2020)
The article aims to discuss the critical force of the Rather Less Than More Project (2014) and the performance One for One - Ruminative Walks (2014) by Portuguese choreographer Vera Mantero. To this end, we began by utilizing the concept methodology knowing from the inside by the anthropologist Tim Ingold, and Maíra Santos’ participation in the project as a performer. From an analysis of the process, the following is discussed: its choreopolitical forces, its projective temporality and a notion of the artist as a curator of him/herself. It is concluded that despite the tensions between art and the logic of production, the work provides several elements in which its force resides: a reflection on politics in art, notions of collaboration, proximity, community, self-learning and responsibility, which distance themselves from empty abstractions.